Chromosome Doubling of Microspore-Derived Plants from Cabbage (Brassica oleracea var. capitata L.) and Broccoli (Brassica oleracea var. italica L.) - Yuan, Suxia; Su, Yanbin; Liu, Yumei; Li, Zhansheng; Fang, Zhiyuan; Yang, Limei; Zhuang, Mu; Zhang, Yangyong; Lv, Honghao; Sun, Peitian (Frontiers in Plant Science, 2015)
Chromosome doubling of microspore-derived plants is an important factor in the practical application of microspore culture technology because breeding programs require a large number of genetically stable, homozygous doubled haploid plants with a high level of fertility. In the present paper, 29 populations of microspore-derived plantlets from cabbage (Brassica oleracea var. capitata) and broccoli (Brassica oleracea var. italica) were used to study the ploidy level and spontaneous chromosome doubling of these populations, the artificial chromosome doubling induced by colchicine, and the influence of tissue culture duration on the chromosomal ploidy of the microspore-derived regenerants. Spontaneous chromosome doubling occurred randomly and was genotype dependent. In the plant populations derived from microspores, there were haploids, diploids, and even a low frequency of polyploids and mixed-ploidy plantlets. The total spontaneous doubling in the 14 cabbage populations ranged from 0 - 76.9%, compared with 52.2 - 100% in the 15 broccoli populations. To improve the rate of chromosome doubling, an efficient and reliable artificial chromosome doubling protocol (i.e., the immersion of haploid plantlet roots in a colchicine solution) was developed for cabbage and broccoli microspore-derived haploids. The optimal chromosome doubling of the haploids was obtained with a solution of 0.2% colchicine for 9 - 12 h or 0.4% colchicine for 3 - 9 h for cabbage and 0.05% colchicine for 6 - 12 h for broccoli. This protocol produced chromosome doubling in over 50% of the haploid genotypes for most of the populations derived from cabbage and broccoli. Notably, after 1 or more years in tissue culture, the chromosomes of the haploids were doubled, and most of the haploids turned into doubled haploid or mixed-ploidy plants. This is the first report indicating that tissue culture duration can change the chromosomal ploidy of microspore-derived regenerants.